The histology and histomorphometry of umbilical cord cross section in preeclampsia and normal pregnancies: a comparative study. (2nd July 2020) - Thomas, Merlin Rachel; Bhatia, Jasvinder Kaur; Kumar, Sushil; Boruah, Dibyajyoti
ABSTRACT: The umbilical cord is the connecting link between the mother and the fetus and its morphology is an indicator of fetal well-being. Preeclampsia is a disorder of pregnancy associated with new-onset hypertension, which occurs most often after 20 weeks of gestation. There are structural differences in the umbilical cord of normotensive and hypertensive pregnant women. This research aimed to study the histology and histomorphometry of umbilical cord areas in preeclampsia and compare the parameters with normal uncomplicated pregnancies of gestational age 37–40 weeks. A total of 70 umbilical cords were studied from preeclampsia ( n = 35) and normal ( n = 35) pregnancies. The parameters studied included cross-sectional areas (CSA) of umbilical cord, umbilical vein lumen, umbilical vein wall, umbilical artery lumen, umbilical artery wall, and Wharton's jelly, including the presence of edema in the vessel walls and Wharton's jelly and basement membrane thickening. The mean umbilical cord CSA was significantly higher in preeclampsia ( p = 0.014). The mean umbilical artery lumen CSA was significantly lower than the normal pregnancy cords ( p = 0.006). The mean Wharton's jelly CSA in preeclampsia was significantly higher than the normal pregnancy cords ( p = 0.004). The parameters for umbilical vein lumen CSA, umbilical vein wall CSA, and umbilical artery wall CSA did not show any significant difference. Histological findings were edema ( p < 0.001) and thickened basement membranes ( p < 0.0001) were considered significant.